Policing and social media : social control in an era of new media - Schneider, Christopher J. (Lexington Books, 2016)
"This book investigates various public aspects of the management, use, and control of social media by police agencies in Canada. This book aims to illustrate the process by which new information technology--namely, social media--and related changes in communication formats have affected the public face of policing and police work. Schneider argues that police use of social media has altered institutional public police practices in a manner that is consistent with the logic of social media platforms. Policing is changing to include new ways of conditioning the public, cultivating self-promotion, and expanding social control. While each case study presented here focuses on a different social media platform or format, his concern is less with the particular format per se, as these will undoubtedly change, and more with developing suitable analytical and methodological approaches to understanding contemporary policing practices on social media sites"--Provided by publisher